Karakterisasi Dan Potensi Pemanfaatan Palm Oil Mill Effluent (POME) Menjadi Bioetanol Dan Biohidrogen - Ramida Elisa Kristiani Simanjuntak; David Andrio; Elvi Yenie (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
The need and consumption of the community for fuel oil (BBM) which is increasing from year to year is inversely proportional to its availability. One alternative energy solution to replace fossil energy is bioethanol and biohydrogen. POME has a high content of organic compounds such as carbohydrates, cellulose, sucrose, and starch so that it has the potential as a substrate for fermentation of bioethanol and biohydrogen. Anaerobic POME processing technology can increase the formation of bioethanol and biohydrogen. This research was conducted by analyzing the characteristics of POME through pH, demand for chemical oxygen (COD) and volatile suspended solids (VSS) and their potential in producing bioethanol and biohydrogen. From this study COD obtained a value of 32000 mg / L. Potential energy of bioethanol and biohydrogen formed through the degradation of organic matter in POME obtained respectively 1700 ml H2 / ml POME / day and 1.35g / L for 8 days Keywords: Acidogenesis, anaerobic, bioethanol, biohydrogen, palm oil mill effluent